Revestimento decorativo monocamada pigmentado, com resíduo de vidro temperado, para aplicação em fachadas - Azevedo, Eriem Allyne Medeiros (2015)
Although efficient from a technical point of view, mortar layers that make up the traditional masonry coating (slurry mortar, plaster and plaster) have to be in contradiction with the new construction technologies and more efficient methods of consumption and work rationalization. From an environmental point of view, the recovery of waste into new composites for the building has been a growing strand of studies in the scientific community, may prove to be a cost-effective solution in some cases. Thus, this research proposes the development of a mortar Decorative Coating Monolayer (RDM), for use in facades, produced on site, incorporating tempered glass waste (RVT) in the cement matrix, as a partial substitute for aggregate. Therefore, we adopted the binder respect / aggregate of 1: 6 (by volume), consistency index 250mm ± 20, sand substitution levels of glass waste 20%, 50% and 80% and relative water / cement varied in many traits. Two additives were used, a polymer, styrene-butadiene-based, and other chemical, besides mineral and silica fume inorganic pigment in colors red, yellow and blue. Mechanical tests were carried out on fresh pasta and hardened, as well as for the applied coating on masonry, so as to demonstrate the feasibility of the material. In addition, it verified the adequacy of the RDM built environment by means of thermal tests. The results demonstrated the feasibility of the proposed RDM with significantly higher values when compared to norms, especially the dash-added replacement content of 20% and addition of pigment in red. Therefore, the study shows the scientific community as an incentive to the use of technological innovations in construction, increasing the range of alternatives available for housing production, with the proposition of a material that achieves the desired functionality and obtain environmental gain, and may be adopted on construction sites as an alternative industrialized mortars.